PTH-208 Home parenteral nutrition (HPN) in palliative oncology patients – a UK single centre case series with survival analysis. (22nd June 2015) - Keane, N; Bertsch, F; Patel, PS; Fragkos, K; Barnova, I; Samaan, M; Morgan, S; Smith, LA; Babbington, M; Di Caro, S; Rahman, F
Abstract : Introduction: HPN support should be a nutritional management strategy in patients who cannot meet their nutritional requirements by oral or enteral routes and those who are eligible to receive therapy outside an acute-care setting. 1 However, use of HPN in incurable patients who cannot eat remains controversial and is only accounted for by approximately 8% of the UK HPN population. 2 We therefore aimed to describe the HPN palliativeoncology cohort at University College London Hospital (UCLH) and identify what factors determine their survival rates and performance status. Method: Data was collected retrospectively and prospectively for palliative oncologypatients receiving HPNthrough hospital computer systems and databases stored by members of the Nutrition team at UCLH between 01/01/2006 to 31/12/2014 (censor date). Survival time was expressed in weeks, Kaplan Meier curves were plotted and performance status was obtained using Karnofsky score (KPS). Results: A cohort of n = 65 (n = 12 active at analysis) palliative oncology patients (male 36.9%, median age 56 years) recieved HPN at UCLH from 2006–2014. Cancers of the following aetiologies comprised most of the cohort: upper gastrointestinal (n = 13, 20%); lower gastrointestinal (n = 15, 23%); and gynaecological (n = 24, 36.9%). The main indicator for HPN was bowel obstruction (n = 44). Overall mean/median survival was 22.4 and 10 weeks (range: 0.4 to 193.3), respectively (Figure 1). Survival also differed by malignancy (mean/median survival-weeks: upper gastrointestinal 10.3/6.4; lower gastrointestinal 24.8/10.7), gynaecological 28.1/8.3). Overall median KPS was 50. The correlation between KPS and survival from discharge to death was r = 0.315 (P < 0.05) in n = 48 patients. Abstract PTH-208 Figure 1 Survival of palliative oncology HPN patients (N = 65) Conclusion: Our results show there is an indication for HPN in palliative oncology patients as it may increase survival period post hospital discharge however this may differ by underlying malignancy. In addition, HPN may improve performance status. Further research is required into patients' quality of life to provide holistic as well as medical insights into HPN in this patient group. Disclosure of interest: None Declared. References: Staun M, et al . ESPEN guidelines on Parenteral nutrition: Home Parenteral Nutrtiion (HPN) in adult patients. Clin Nutr. 2009:467–479 BANS: Annual BANS Report, 2011; Artificial Nutrition Support in the UK 2000–2010. www.bapen.org.uk